The genus Leptodora Lilljeborg (Crustacea: Branchiopoda: Cladocera) is not monotypic: description of a new species from the Amur River basin (Far East of Russia) - Korovchinsky, Nikolai M. (Zootaxa, 2009)
New species, Leptodora richardi sp. nov., is described from some large lakes and other water bodies of the Lower Amur River basin. It differs from L. kindtii Focke, the only species known in this genus until now, by a smaller body size and proportions of some body parts, namely a comparatively longer head and shorter abdomen, and by presence of fine setules on the end of anterior distal seta of second segment of thoracic limbs of first pair. Small differences in male features require further elucidation. Among the investigated populations of L. kindtii, one of them from the Volga Delta was analyzed in more detail due to the unusually small size of their adults, comparable with those of L. richardi sp. nov., but had body proportions characteristic of the former species and probably represented its extreme morpho-ecological variation. L. kindtii is widely distributed in Palearctic, while L. richardi sp. nov. seems to be an endemic of East Asia probably distributed from the Lower Amur River in the Far East of Russia to Eastern China and Japan (Honshu Island) in the south.